Utilitarian and hedonic values of eWOM media and online booking decisions for tourist destinations in India - Amit Tariyal; Swati Bisht; Vinay Rana; Santanu Roy; Sumit Pratap (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
In this contemporary world, electronic word of mouth (eWOM) platforms (or media) have become a prerequisite information source for online surfers, especially when planning excursions. However, tourists refer to the reviews of these platforms based on utilitarian and hedonic aspects. The utilitarian value enhances users' task performance, whereas the hedonic value is related to pleasure and inner feelings. The present work was undertaken to study the importance of various utilitarian and hedonic determinants, and analyses their influence on the perceived usefulness (PU) of eWOM media and subsequent online booking decisions (OBD) for tourist destinations in India. In addition, the study investigates whether the influence of PU of eWOM media on OBD varies according to gender. A conceptual model was introduced based on data analysis done through SPSS 23 and AMOS 23. The model was empirically validated based on sample data comprising 338 Indian tourists. The purposive sampling technique was used in the current study, and only those samples who referred to eWOM media for information search were accepted. The findings indicate that utilitarian and hedonic determinants significantly influence tourist decision-making. TripAdvisor was the most popular web portal, followed by other social networking sites among the preferred sources of tourist destination information. The moderating analysis revealed that the impact of eWOM media PU on OBD was higher in males than in females. The study suggests that website designers and administrators design the contents according to the needs identified.
Keywords: 650; eWOM media; gender; hedonic value; online booking decision; perceived usefulness; tourist destination; utilitarian value